2016
DOI: 10.1186/s13075-016-1015-0
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide versus mycophenolate mofetil in scleroderma interstitial lung disease (SSc-ILD) as induction therapy: a single-centre, retrospective analysis

Abstract: BackgroundScleroderma is a systemic autoimmune disease characterized mainly by skin manifestations and involvement of various visceral organs, especially the lungs. Lung involvement is the leading cause of mortality in patients with scleroderma. There are data to suggest that cyclophosphamide (CYC) and mycophenolate mofetil (MMF) are effective in the management of scleroderma interstitial lung disease (SSc-ILD) but no head to head comparative data are available to date.MethodsFor the last 3 years, patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 20 publications
(15 reference statements)
0
18
0
2
Order By: Relevance
“…Interestingly, of the five studies that cited prior validation to justify their choice of PFT (% predicted FVC in four cases [69,111,114,149] and % predicted DLCO in one) [33], only the study using % predicted DLCO referenced an article with reported measures of validity. The four studies which chose their main PFT outcome measure based on its high sensitivity (in the case of DLCO) [11,14] or its high specificity (in the case of FVC) [128,169] either did not provide a citation to support this claim [169], referred to studies performed outside the field of SSc-ILD [11,14,128], or cited SSc studies with fewer than 20 patients [11,14].…”
Section: Outcome Study Resultsmentioning
confidence: 99%
“…Interestingly, of the five studies that cited prior validation to justify their choice of PFT (% predicted FVC in four cases [69,111,114,149] and % predicted DLCO in one) [33], only the study using % predicted DLCO referenced an article with reported measures of validity. The four studies which chose their main PFT outcome measure based on its high sensitivity (in the case of DLCO) [11,14] or its high specificity (in the case of FVC) [128,169] either did not provide a citation to support this claim [169], referred to studies performed outside the field of SSc-ILD [11,14,128], or cited SSc studies with fewer than 20 patients [11,14].…”
Section: Outcome Study Resultsmentioning
confidence: 99%
“…4 In other reported studies, pulmonary function has also improved or stabilized after treatment with at least more than 2 g/day of MMF. [15][16][17][18] The SLS II study has shown an average peak improvement of FVC at 18-21 months. The Australian Scleroderma Cohort study has demonstrated that treatment with MMF was associated with stability of the SSc-ILD for up to 36 months.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective or openlabel prospective studies in SSc and SSc-ILD have shown that MMF improved skin score and stabilized pulmonary function. [35][36][37] More importantly, it improved a 5-year survival. Recently a randomized, double-blind, parallel group trial that compared 2 years of oral MMF (target dose 3gr/day) to oral CYP (2 mg/kg/ day) for 1 year followed by placebo was conducted.…”
Section: Mycophenolate Mofetil Mycophenolate Mofetil (Mmf)mentioning
confidence: 92%